Language style used by Kamala Khan in selected episodes of Ms. Marvel TV series : A Sociolinguistic Analysis - Meivilana Stela Sani (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2022)
et,1/ yna, c.1